PEDAGOGICAL MANAGEMENT STRATEGY: THE FUNDAMENTAL BASIS FOR OPTIMIZING SCHOOL COEXISTENCE - Pinzón, Evánngelina; Portilla, Hugo (Revista Arbitrada Formación Gerencial, 2022)
This article aims to analyze Pedagogical management strategy: fundamental basis for optimizing School Coexistence; Was based on the positivist philosophy established under the positivist philosophy, developed as an explanatory research, with a non-experimental, transectional field design. The population was represented by 7 Directors and 28 Teachers. For the information collection, a closed question instrument was applied with simple selection, consisting of thirtysix (36) items versioned. It is concluded that managers and teachers should develop activities such as directed knowledge aggories, coexistence laboratories and experiences, didactic classrooms and coexistence management indicators. It is urged to implement the design made on pedagogical strategies as tools to improve school coexistence in educational institutions.